Experimental and Numerical Investigation on Infilled Vertical Well LASER-Assisted SAGD - Ding Chao; Wu Yongbin; Yang Guo; Luo Chihui (Geofluids)
In the SAGD process with dual horizontal wells in heterogeneous reservoirs, the injection pressure of steam huff-n-puff by infilled interwell vertical wells is too high, and the heat communication between SAGD wellpairs and infilled wells is too long, which leads to a series of problems. The solvent-assisted vertical well stimulation (LASER) technology is proposed to solve the problems above. The solvent formula was optimized, and its key mechanism was studied by viscosity reduction experiments, multicomponent phase behavior experiments at high temperature and high pressure, and scaled two-dimensional physical experiments. The experimental results show that when adding 10% 2# or 3# solvent oil, the viscosity reduction of crude oil can reach 96.65% and 96.73%, respectively. The HTHP visualized phase behavior experiment results show that the mixture of low flash point solvent oil 2# with high flash point solvent oil 3# (volumetric ratio 3 : 2) has excellent high temperature oil solubility stability and is similar to water vapor phase behavior, so it is determined as the ideal formula. The scaled two-dimensional physical experiment results show that the solvent-assisted vertical well huff-n-puff has the key mechanism of reducing injection pressure and porous flow resistance, expanding the sweep region of injected fluid and accelerating thermal communication. The cycle of huff-n-puff was reduced from 6 to 3, which greatly shortened the thermal communication time. From the scaled physical experiments, the oil rate and the oil recovery of SAGD were improved by 19.86% and 6.3%, respectively. Field-scale numerical simulation was performed, and the production performance compared with SAGD and conventional infilled CSS-SAGD was investigated, which shows that by adding solvent into steam stimulation, 6 cycles were reduced, and the incremental oil recovery factor was 27.3% and 13.2%, respectively. The performance of accelerating thermal communication and production improvement by LASER has been validated by 4 SAGD wellpairs in field practice, and its long-term prediction result shows significant potential in similar heterogeneous SAGD reservoirs.